Are You A Shopaholic? A Case Study of Customer Satisfaction of Shopee - Huei, Lok Yee; Ling, Lim Hui; Ibrahim, Najwa Irdina Binti; Sarudin, Muhammad Talhah Bin; Halim, Nabila Husna Binti Abdul; Shahaidil, Nawal Nadiah Binti Md; Permana, Michael Aditya Surya; Ramekar, Bhushan Arun; Aradhya, BN Nishchith (International Journal of Tourism and Hospitality in Asia Pasific, 2023)
Online shopping or called e-shopping is the place for everyone to purchase goods or services via an application provided or through a web browser over the Internet. One of the biggest e-commerce sites in Southeast Asia, Shopee has locations around the globe, including Malaysia, Indonesia, Taiwan, Thailand, Vietnam, and Singapore. It is an online application where everyone can buy and sell goods easily with just one click on their smartphone. This case study examines the significant factors toward customers’ satisfaction with using Shopee in Malaysia. In this case study, the researchers use a questionnaire survey to accumulate information from 100 customers of the Shopee application to know deeper about their satisfaction with using Shopee for online purchases in Malaysia. The findings show that promotion strategy, service quality, and product variety, affecting the customers’ satisfaction of Shopee. The results provide new insights into customers’ satisfaction that can help the company's performance in the future.